PENGGUNAAN MODEL PEMBELAJARAN TALKING STICK TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN EKONOMI KELAS X MIPA SMAN 1 KOTA JAMBI - Miko Anggara, Kasiono (SJEE (Scientific Journals of Economic Education), 2020)
Abstract This study aims to reveal the extent of the influence of the use of cooperative learning models on student learning outcomes in economics taught by the cooperative learning model type of Talking Stick class X MIPA in SMA Negeri 1 Jambi City. The results showed that there was a very significant effect on student learning outcomes in Economics and Mathematics X class in SMA Negeri 1 Jambi City. Based on the results of data processing analysis, it is known that the mean value of the learning outcomes (Pre-Test) is 51.32. While the mean value calculated (mean) learning outcomes (PostTest) is 71.25. Thus, it can be concluded that the Talking Stick type of cooperative learning model influences economic learning outcomes. Keywords: Talking Sticks, Learning Outcomes